The influence of medical and social risk factors on the development of hypertension in the adult population at the regional level - Lashkul, Z. V.; Lashkul, D. A.; Лашкул, З. В.; Лашкул, Дмитро Андрійович; Лашкул, Д. А. (Запорізький державний медичний університет, 2021)
The aim of the study was to investigate the impact of medical and social risk factors (RF) on the development of arterial hypertension (AH) in the adult population at the regional level (Zaporizhzhia, Ukraine). Materials and methods. The study, after obtaining an informed consent, involved 2000 patients, residents of Zaporizhzhia region, including 1000 patients (522 men and 478 women, mean age 51.60 ± 0.85 years) with AH and 1000 patients (478 men and 522 women, mean age 49.80 ± 0.94 years) without AH. The relationship between hypertension and the action of already known RF, the reliable connection of which has been proven by many studies, including burdened heredity, overweight, excessive alcohol consumption, smoking, physical inactivity, and some social and economic RF. In order to achieve the goal of the study, we used a set of general scientific and special interrelated and consistently applied methods: system analysis, bibliosemantic, descriptive statistics, calculating the odds ratio (OR) of the event with a 95 % confidence interval (CI); values of P to define statistical significance. Results. According to our study, the simple logistic regression analysis of persons from the study cohort reveals a reliable relationship (P < 0.05) between AH and family history of hypertension, overweight, physical inactivity, smoking. Along with the well-known RF, the residents of the Zaporizhzhia region are exposed to other social and economic RF, in particular, poor living standards (OR 2.45; 95 % CІ 2.04–2.94; P < 0.0001), unemployment (OR 1.9; 95 % CІ 1.38–2.64; P < 0.0001), lack of healthcare facilities at the place of residence (OR 0.29; 95 % CІ 0.22–0.35; P < 0.0001), low level of education (OR 2.39; 95 % CІ 1.97–2.91; P < 0.0001). Conclusions. It has been found that along with the traditional risk factors, the residents of the Zaporizhzhia region have other social and economic risk factors, including poor living standards, low average income, unemployment, lack of healthcare facilities at the place of residence, low level of education. Мета роботи – вивчення впливу медико-соціальних факторів ризику (ФР) на розвиток артеріальної гіпертензії (АГ) у дорослого населення на регіональному рівні (м. Запоріжжя, Україна). Матеріали та методи. Здійснили дослідження, в якому після підписання інформованої згоди взяли участь 2000 пацієнтів, жителів Запорізької області: 1000 пацієнтів (522 чоловіки та 478 жінок, середній вік – 51,60 ± 0,85 року) з АГ і 1000 пацієнтів (478 чоловіків і 522 жінки, середній вік – 49,80 ± 0,94 року) без АГ. Вивчили зв’язок між АГ і дією відомих ФР, вірогідний зв’язок яких доведено багатьма дослідженнями: обтяженою спадковістю, надмірною вагою, надмірним вживанням алкоголю, курінням, гіподинамією, низкою ФР соціально-економічної спрямованості. Під час дослідження використали комплекс взаємопов’язаних і послідовно застосованих загальнонаукових і спеціальних методів: системний аналіз, бібліосемантичний, описову статистику, розраховували відношення шансів (ВШ) виникнення події з 95 % довірчим інтервалом (ДІ), р – рівень значущості. Результати. У досліджуваній когорті під час простого логістичного регресійного аналізу виявили вірогідний (р < 0,05) зв’язок між АГ та обтяженою спадковістю, надмірною вагою, гіподинамією, курінням. Крім відомих ФР, для мешканців Запорізької області притаманні й інші ФР соціально-економічної спрямованості, як-от незадовільний рівень життя (ВШ 2,45; 95 % ДІ 2,04–2,94; p < 0,0001), безробіття (ВШ 1,9; 95 % ДІ 1,38–2,64; p < 0,0001), відсутність закладів охорони здоров’я в місці проживання (ВШ 0,29; 95 % ДІ 0,22–0,35; p < 0,0001), низький рівень освіти (ВШ 2,39; 95 % ДІ 1,97–2,91; p < 0,0001). Висновки. Поряд із традиційними факторами ризику для мешканців Запорізької області притаманні й інші фактори ризику соціально-економічної спрямованості: незадовільний рівень життя, низький середній дохід, безробіття, відсутність закладів охорони здоров’я в місці проживання, низький рівень освіти. Цель работы – изучение влияния медико-социальных факторов риска (ФР) на развитие артериальной гипертензии (АГ) у взрослого населения на региональном уровне (г. Запорожье, Украина). Материалы и методы. Проведено исследование, в котором после подписания информированного согласия приняли участие 2000 пациентов, жителей Запорожской области: 1000 пациентов (522 мужчины и 478 женщин, средний возраст – 51,60 ± 0,85 года) с АГ и 1000 пациентов (478 мужчин и 522 женщины, средний возраст – 49,80 ± 0,94 года) без АГ. Изучена связь между АГ и действием уже известных ФР, достоверная связь которых доказана многими исследованиями: наследственностью, избыточным весом, избыточным употреблением алкоголя, курением, гиподинамией, рядом ФР социально-экономической направленности. В ходе исследования использовали комплекс взаимосвязанных и применяемых последовательно общенаучных и специальных методов: системный анализ, библиосемантический, описательную статистику, рассчитывали отношение шансов (ОШ) возникновения события с 95 % доверительным интервалом (ДИ), р – уровень значимости. Результаты. В исследуемой когорте при простом логистическом регрессионном анализе установлена достоверная связь (p < 0,05) между АГ и наследственностью, избыточным весом, гиподинамией, курением. Наряду с известными ФР, для жителей Запорожской области присущи и другие ФР социально-экономической направленности: неудовлетворительный уровень жизни (ОШ 2,45; 95 % ДИ 2,04–2,94; p < 0,0001), безработица (ОШ 1,9; 95 % ДИ 1,38–2,64; p < 0,0001), отсутствие учреждений здравоохранения в месте проживания (ОШ 0,29; 95 % ДИ 0,22–0,35; p < 0,0001), низкий уровень образования (ОШ 2,39; 95 % ДИ 1,97–2,91; p < 0,0001). Выводы. Установлено, что наряду с традиционными факторами риска для жителей Запорожской области присущи и другие факторы риска социально-экономической направленности, в том числе неудовлетворительный уровень жизни, низкий средний доход, беtзработица, отсутствие учреждений здравоохранения в месте проживания, низкий уровень образования.
Вплив медико-соціальних факторів ризику на розвиток артеріальної гіпертензії в дорослого населення на регіональному рівні
Влияние медико-социальных факторов риска на развитие артериальной гипертензии у взрослого населения на региональном уровне
Лашкул Д. А. - ORCID ID: 0000-0001-7802-3550
Keywords: hypertension; risk factors; primary prevention; артеріальна гіпертензія; фактори ризику; профілактика; артериальная гипертензия; факторы риска; профилактика